Silencing of D-Lactate Dehydrogenase Impedes Glyoxalase System and Leads to Methylglyoxal Accumulation and Growth Inhibition in Rice - An, Baoguang; Lan, Jie; Deng, Xiaolong; Chen, Silan; Ouyang, Chao; Shi, Huiyun; Yang, Jing; Li, Yangsheng (Frontiers in Plant Science, 2017)
D-Lactate is oxidized by two classes of D-lactate dehydrogenase (D-LDH), namely, NAD-dependent and NAD-independent D-LDHs. Little is known about the characteristics and biological functions of D-LDHs in rice. In this study, a functional NAD-independent D-LDH (LOC_Os07g06890) was identified in rice, as a result of alternative splicing events. Characterization of the expression profile, subcellular localization, and enzymatic properties of the functional OsD-LDH revealed that it is a mitochondrial cytochrome-c-dependent D-LDH with high affinity and catalytic efficiency. Functional analysis of OsD-LDH RNAi transgenic rice demonstrated that OsD-LDH participates in methylglyoxal metabolism by affecting the activity of the glyoxalase system and aldo-keto reductases. Under methylglyoxal treatment, silencing of OsD-LDH in rice resulted in the accumulation of methylglyoxal and D-lactate, the decrease of reduced glutathione in leaves, and ultimately severe growth inhibition. However, the silencing of OsD-LDH did not affect the growth under photorespiration conditions. Our results provide new insights into the role of NAD-independent D-LDHs in rice.